Classification Formula and Generation Algorithm of Cycle Decomposition Expression for Dihedral Groups - Dakun Zhang; Yonggang Lin; Guozhi Song (Abstract and Applied Analysis)
The necessary of classification research on common formula of group (dihedral group) cycle decomposition expression is illustrated. It includes the reflection and rotation conversion, which derived six common formulae on cycle decomposition expressions of group; it designed the generation algorithm on the cycle decomposition expressions of group, which is based on the method of replacement conversion and the classification formula; algorithm analysis and the results of the process show that the generation algorithm which is based on the classification formula is outperformed by the general algorithm which is based on replacement conversion; it has great significance to solve the enumeration of the necklace combinational scheme, especially the structural problems of combinational scheme, by using group theory and computer.